DISKURSUS SEPUTAR LITERATUR TAFSIR AHKAM - Isnan Anshory (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2023)
This paper explains that the discourse around the interpretation of ahkam has developed into various literacy variants which are concluded in two patterns; first: literacy based on the affiliation of interpreter schools, and second: literacy based on the systematics of composing interpretive works. For the first pattern, it is concluded that there are 4 schools of thought that have contributed greatly to the development of literary discourse on akhkam interpretation, namely the Hanafi school of thought, the Maliki school of thought, the Syafi'i school of thought and the Hanbali school of thought. As for the second pattern, it is concluded that there are two approaches to the systematic preparation of ahkam interpretations, namely the tabwib fiqih approach and the tartib mushafi approach.